COMPARISON OF LAPAROSCOPIC AND OPEN APPENDECTOMY IN TERMS OF SURGICAL SITE INFECTION - ULLAH , R; SHAH , M; BABAR , Y; KHAN , A (Biological and Clinical Sciences Research Journal, 2024)
Appendectomy is a common surgical procedure, and the choice between laparoscopic and open approaches has clinical significance. Surgical site infection (SSI) is a critical postoperative complication. This study aimed to compare laparoscopic and open appendectomy in terms of SSI rates. A prospective observational study was conducted at multiple centers including Department of General Surgery, MRHSM Hospital Pabbi Nowshera, Jinnah Teaching Hospital Peshawar and Cat C Hospital Tangi Charsadda, DHQ Hospital Daggar Buner, Khyber Pakhtunkhwa Pakistan in the duration from July, 2023 to December, 2023. The research is involving 320 patients aged 14 to 64 years. Data included demographic information, surgical approach, operative time, hospital stay, and SSI severity using the Southampton grading system. Statistical analysis was performed using SPSS. Laparoscopic (Group A, n=110) and open (Group B, n=210) appendectomies were compared. Group A had a shorter hospital stay (p < 0.05) and similar operative times. SSI rates favored laparoscopic surgery (p < 0.05), with fewer patients developing infections within 10 days post-surgery. Laparoscopic appendectomy demonstrated reduced SSI risk and improved postoperative outcomes. Laparoscopic appendectomy is associated with lower SSI rates, shorter hospital stays, and comparable operative times compared to open appendectomy. These findings support the preference for laparoscopic surgery, especially in low-risk patients, to enhance postoperative outcomes.